The Correlation Between the Narrative Structure and the Rhetorical Elements in the Story of Ashab Al-Kahf - Muzammir, Anas; Zulazhan, Ab. Halim; Badri Najib, Zubir (2015)
This paper discusses the structural narrative and rhetorical aspects as well as the correlation found between the two elements in the English version of the story ‘The Companions of Cave’. This story is unfolded in Surah al-Kahf (The Cave) in the Qur’an. It aims to reveal various aspects of rhetorical styles used in the story. In addition, the narrative structure for each plot is further examined, and the rhetorical elements are explored to reveal its beauty, refinement and subtlety, as well as its function and role in supporting the narrative structure. To achieve these objectives, the study deliberated both its linguistic and situational contexts to reveal its congruency within the narrative elements, and offer explanation on why it appears to be so in the Qur’an.